2016
DOI: 10.1021/acsnano.6b02547
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Bioelectronic Tongue for Sensing Umami and Sweet Tastes Based on Human Taste Receptor Nanovesicles

Abstract: For several decades, significant efforts have been made in developing artificial taste sensors to recognize the five basic tastes. So far, the well-established taste sensor is an E-tongue, which is constructed with polymer and lipid membranes. However, the previous artificial taste sensors have limitations in various food, beverage, and cosmetic industries because of their failure to mimic human taste reception. There are many interactions between tastants. Therefore, detecting the interactions in a multiplexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…Mammals are sensitive to sweet taste because of advanced evolution of sweet taste receptors on the taste buds ( Ahn et al., 2016 ). Unlike mammals, chickens are lacking T1R2, one of the taste receptor family gene responding to sweeteners in mammals ( Shi and Zhang, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammals are sensitive to sweet taste because of advanced evolution of sweet taste receptors on the taste buds ( Ahn et al., 2016 ). Unlike mammals, chickens are lacking T1R2, one of the taste receptor family gene responding to sweeteners in mammals ( Shi and Zhang, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3a shows a schematic of the immobilization of the nanovesicles on graphene electrode (GE). Based on our previous research 38 , the CVD-grown graphene was in the form of a single layer. Therefore, the thickness of the graphene channel was estimated to be about 0.8 nm, which is the thickness of a single layer of graphene.…”
Section: Construction Of Human Hormone Receptor-carrying Nanovesiclesmentioning
confidence: 99%
“…In addition, graphene provides excellent sensitivity, stability and a rapid response [34][35][36][37] . Previous study has shown that biosensor using graphene-FET and human GPCR-carrying nanovesicles exhibit excellent sensor characteristics 38 . Here, two kinds of hormone sensors were successfully demonstrated to detect PTH and GCG using graphene FET sensors fabricated with PTHR-and GCGR-carrying nanovesicles.…”
mentioning
confidence: 99%
“…Thus, this has prompted their expanded use in the construction of electrochemical biosensors with enhanced analytical performance 41 44 . Thus far, the immobilization of two types of nanovesicles, which have human T1R2/T1R3 for the umami taste and sweet taste on their membranes, onto graphene surfaces for the simultaneous detection of umami and sweet tastants have been reported 45 . However, the immobilization of human T1R2 onto GO in the presence of ZnONPs and MWCNT for the detection of Reb-A is still unreported in literature.…”
Section: Introductionmentioning
confidence: 99%